In defense of the critical philosophy: On Schelling's departure from Kant and Fichte in Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (1796/1797) - Harry, C.C. (Journal of Speculative Philosophy, 2015)
This article considers the second treatise of Schelling's Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (Treatises Explaining the Idealism of the Science of Knowledge, 1796/97), a lesser-known work from the early Schelling. Here, Schelling proposes to defend the critical position insofar as it purports to be a system based on human reason, but instead he issues a backhanded critique of the assumption on behalf of the critical philosophers to try and limit the bounds of pure reason by means of their own use of reason. Schelling then offers an alternative way to think about the relationship of mind (Geist) and matter in nature. This article argues that Schelling's actual explanation of the critical philosophy as a position founded by reasonable minds ultimately belies his promise to defend it, thus calling into question that Schelling's thought prior to 1800 was a mere reiteration of Kantian/Fichtean transcendentalism. Copyright © 2015 The Pennsylvania State University, University Park, PA.
Keywords: Critical philosophy; Fichte; Kant; Naturphilosophie; Shelling; dept.phi